Supporting innovation pathways for sustainable agriculture intensification: Lessons from cross country evidence - Kohl, R. (Commission on Sustainable Agriculture Intensification, 2022)
This paper takes a first step in filling that gap in terms of assessing whether there is evidence to support proposals about how agricultural innovation pathways should be pursued. We have looked at the recent literature that proposes principles and approaches to achieving large-scale sustainable agriculture intensification (SAI), and disaggregated these all-inclusive approaches into individual components and hypotheses. We then tested six hypotheses through case studies of innovation pathways, trajectories, scaling and other attempts at achieving large-scale SAI. These cases come from three CoSAI-commissioned country studies in Brazil (Chiodi Bachion et al. 2022), India (Khandelwal et al. 2022) and Kenya (Mati et al. 2022), and five studies of the scaling of individual agricultural innovations commissioned by USAID’s Bureau of Resilience and Food Security (Kohl 2016a, 2016b, 2016c; Foy 2017; Foy and Wafula 2016).